Dataset for: Biodegradation of Crude Oil and Corexit 9500 in Arctic seawater - Matt Perkins (Gulf of Mexico Research Initiative, 2017)
Arctic seawater was collected from two locations (nearshore and offshore) and laboratory mesocosms were conducted to assess the extent of degradation to Alaska North Slope crude oil and the surfactant components of Corexit 9500 (DOSS, Span 80, Tween 80 and Tween 85) and to assess changes in the microbial community, specifically bacterial community structure (16S rRNA genes) and abundance of biodegradation genes (GeoChip 5.0 microarray). This dataset supports the publication: McFarlin, K. M., Perkins, M. J., Field, J. A., & Leigh, M. B. (2018). Biodegradation of Crude Oil and Corexit 9500 in Arctic Seawater. Frontiers in Microbiology, 9. doi:10.3389/fmicb.2018.01788